A Temperature Control System for Near Infrared Spectroscopic Analysis using Proportional Controller - Chia, Kim Seng (International Journal of Integrated Engineering, 2017)
Near Infrared Spectroscopy (NIRS) has been widely investigated as an alternative to replace conventional chemical analysis. However, NIRS analysis is susceptible to the change of surrounding temperature. This will affect the NIRS analysis and cause the result inconsistent. Therefore, this paper presents a work in designing the temperature control system for NIRS data acquisition. First, the cooling element of the system was designed using a TEC1-12706 Peltier as a cooling element, and a temperature sensor LM35 was used to measure the temperature inside the data acquisition container. The PWM signal of microcontroller was used to control the N-channel MOSFET so that the desired temperature can be achieved. The Arduino Uno was used as the microcontroller of the system. Lastly, a Proportional Controller was applied for forming the temperature control system in the container and the performance of the system was analysed. Results show that the Proportional Controller outperformed to Logic controller. Findings indicate that the proposed control system with optimal Kp value is able to maintain the desired temperature.